Rethinking the law of armed conflict in an age of terrorism - Ford, Christopher; Cohen, Amichai (Lexington Books, 2012)
Ten years after the terrorist attacks of September 11, 2001, Rethinking the Law of Armed Conflict in an Age of Terrorism, edited by Christopher Ford and Amichai Cohen, brings together a range of interdisciplinary experts to examine the problematic encounter between international law and challenges presented by conflicts between developed states and nonstate actors, such as international terrorist groups. Through examinations of the counter-terrorist experiences of the United States, Israel, and Colombia--coupled with legal and historical analyses of trends in international humanitarian law--the authors place post-9/11 practice in the context of the international legal community's broader struggle over the substantive content of international rules constraining state behavior in irregular wars and explore trends in the development of these rules.--Résumé de l'éditeur